SOCIAL WORK AND ENVIRONMENT: AN ECOSOCIAL APPROACH (Third Sector Social Economic Review, 2017)
Abstract: This article draws on insights from social work, ecopsychology and ecofeminism to inform an ecosocial approach honouring humans’ interconnectedness with nature. It reexamines social work’s ecosystems perspective and redefines its central ‘person-in-environment’ configuration to embrace a broadened emphasis on the natural world. It identifies insights from ecofeminism on the parallels between the oppression of women and domination of nature, and presents feminist ways of relating that may enhance connection with the planet as a whole. It introduces the concepts of empathy and empowerment from relational cultural theory as important ideas to integrate with social work’s ecosystems perspective to promote deeper awareness of this connection. Finally, the ecosocial approach is examined as a means of promoting environmental sustainability at all levels of social work practice.
Keywords: Person-in-environment; ecosocial approach; social work; ecopsychology; ecofeminism